Peningkatan Ketersediaan Fosfor Tanah dan Tanaman serta Hasil Padi Sawah pada Inceptisols asal Jatinangor Melalui Aplikasi Pembenah Tanah dan Pemupukan - Sofyan, Emma Trinurani; Sudirja, Rija; Setiawan, Ade; Puspasari, Lindung Tri; Zahra, Siti Revita (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Inceptisols is a soil order that usually low in organic matter and nutrient content. This condition resulted to dominantly sub optimal soil that is required to be amended prior cultivation process.Inceptisols properties can be enhanced through the addition of organic matter such as water hyacinthcompost, straw biochar, humic acid, and guano. Besides organic matter, the integration of NPKfertilizer can improve the chemical and physical characteristics of the soil, nutrient availability, andoptimize rice productivity in Inceptisols. This experiment aimed to identify the optimal dosage of soilamendments in combination with N, P, and K fertilizers to maximize phosphorus availability in the soiland plants, as well as rice yields in Inceptisols. This experiment took place from September 2025 toJanuary 2026 at the Soil Chemistry and Plant Nutrition Laboratory Experimental Garden, Faculty ofAgriculture, Universitas Padjadjaran, Jatinangor, Sumedang. The experiment used a RandomizedComplete Block Design with six treatments and four replications, that is: control; recommended N, P,K; soil amendment; ½ soil amendment + ¾ dose of N, P, K; 1 soil amendments + ½ dose of N, P, K; 1 ½soil amendment + ¼ dose of N, P, K. One dose of soil amendment used was 8000 kg ha-1, while one doseof N, P, K fertilizer was 350 kg ha-1 Urea, 50 kg ha-1 SP-36, and 50 kg ha-1 KCl. The results of theexperiment showed that the dose of 1 soil amendment + ½ dose of N, P, K yielded a percentage of grainper panicle of up to 94.75% and provided the highest available P and P uptake by plants.